A case study on the implementation of Qardhul Hasan concept as a financing product in Islamic Banks in Malaysia - Zainal Abidin, Ahmad; Mohd Alwi, Norhayati; Mohd. Ariffin, Noraini (International Islamic University Malaysia, 2011)
Qardhul Hasan is a zero-return financing that Al-Quran urges Muslims to make available to those who need it. In addition, Qardhul Hasan is an example of a unique instrument offered by Islamic Financial Institutions (“IFIs”) due to non involvement of interest. The objective of this paper is to study the implementation of Qardhul Hasan concept, as a financing product in an Islamic bank in Malaysia. This study adopted a single case study research. This is the best approach and appropriate to answer the research questions and to achieve the research objectives. In addition, this is a pilot case study which can be extended for multiple case studies later. This study reveals that CALF Berhad offers Qardhul Hasan financing only to its employees. In addition, the facility is limited for certain purposes like marriage, birth of a child, study and other relevant purposes. The study also offers guidelines on the implementation process of the Qardhul Hasan financing in IFIs. Hence it is also believed that this study can be used by the regulatory body like Bank Negara Malaysia or Malaysian Accounting Standard Board, as a basis for setting up the accounting and reporting guidelines, specifically on Qardhul Hasan.